Urban nitrogen budgets: flows and stock changes of potentially polluting nitrogen compounds in cities and their surroundings - a review - Winiwarter, Wilfried; Amon, Barbara; Bai, Zhaohai; Greinert, Andrzej; Kaltenegger, Katrin; Ma, Lin; Myszograj, Sylwia; Schneidergruber, Markus; Suchowski-Kisielewicz, Monika; Wolf, Lisa; Zhang, Lin; Zhou, Feng (Journal of integrative environmental sciences, 2020)
Concepts of material flow and mass consistency of nitrogen compounds have been used to elucidate nitrogen's fate in an urban environment. While reactive nitrogen commonly is associated to agriculture and hence to large areas, here we have compiled scientific literature on nitrogen budget approaches in cities, following the central role cities have in anthropogenic activities generally. This included studies that specifically dealt with individual sectors as well as budgets covering all inputs and outputs to and from a city across all sectors and media. In the available data set, a clear focus on Asian cities was noted, making full use of limited information and thus enable to quantitatively describe a local pollution situation. Time series comparisons helped to identify trends, but comparison between cities was hampered by a lack of harmonized methodologies. Some standardization, or at least improved reference to relevant standardized data collection along international norms was considered helpful. Analysis of results available pointed to the following aspects that would reveal additional benchmarks for urban nitrogen budgets: analysing the share of nitrogen that is recycled or reused, separating largely independent sets of nitrogen flows specifically between food nitrogen streams and fossil fuel combustion-related flows, and estimating the stock changes for the whole domain or within individual pools.